Modeling Cell Communication by Communication Engineering - Liu, Jian-Qin; Yue, Wuyi (Modeling, Methodologies and Tools for Molecular and Nano-scale Communications, 2017)
In molecular biology of the cell, cell communication is defined as the process carried out by chemical signals within and among cells. The informatics issue of cell communication in this book chapter is to uncover the principles of the bioinformatics of cell communication by means of communication engineering, e.g., the statistical tool for performance analysis of communication processes. As we know well by now, the state of the art of molecular science has been reshaped by advanced technologies since the genome sequencing became a reality. In accordance with nowadays available nanotechnology for molecular signal detection, we apply communication engineering technology in the theoretical analysis of cell communication whose goal is to discover the mechanism of cell communication that determines the cellular functions connected with applications in medicine. Though intensive research has been devoted to the biochemistry of signaling pathways, laying a strong scientific foundation for the informatics study of communication processes of the cell in the form of signaling pathways, the study of the communication mechanism of signaling pathway networks in the cell—cell communication—by means of communication engineering is still a relatively new field, where supporting technologies from multiple disciplines are needed. In this book chapter, the formulation of the cell communication mechanism of signaling pathway networks using martingale measures for random processes is proposed and the performance of the cell communication system constructed by the signaling pathways in simulation studies is evaluated from the viewpoint of communication engineering. From the computational analysis result of the above cell communication process, it is concluded that the modeling method in this study not only is efficient for bioinformatics analysis of biological cell communication processes but also provides a reference framework for brain communication towards its application in molecular biomedical engineering.